Comprehensive food security and vulnerability analysis (CFSVA): Democratic Republic of Congo - Akakpo, Koffi; Randriamamonjy, Josee; Ulimwengu, John M. (World Food Programme, 2014)
This report includes specific findings on the number of food insecure and vulnerable people in the country, the geographic distribution of the food insecure and vulnerable groups, their characteristics, their capacity to manage shocks, and the driving forces of food insecurity and vulnerability. It includes additional findings from the Multiple Indicator Cluster Survey (MICS, 2010) and the Demographic and Health Survey (DHS, 2007).